1997
DOI: 10.1557/jmr.1997.0019
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial dependence of the melting behavior of In nanoparticles embedded in Al matrices

Abstract: Nanometer-sized In particles (5−45 nm) embedded in the Al matrix were prepared by using melt-spinning and ball-milling techniques. Different crystallographic orientationships between In nanoparticles and the Al matrix were constructed by these two approaches. Melting behavior of the In particles were investigated by means of differential scanning calorimetry (DSC). It was found that the epitaxially oriented In nanoparticles (with the Al matrix) in the melt-spun sample were superheated to about 0−38 °C, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 23 publications
(27 reference statements)
2
58
0
Order By: Relevance
“…The m(z) modification matches closely the measurement of Ga [19][20][21][22][23][24][25][26][27][28][29][30][31] , and Sn 500 clusters, and Sn nanosolids deposited on Si 3 N 4 substrate as well [64]. Calculations [100] show that the T m transition for Sn 6-13 happens at Sn 7 .…”
Section: Bols Formulationsupporting
confidence: 77%
See 2 more Smart Citations
“…The m(z) modification matches closely the measurement of Ga [19][20][21][22][23][24][25][26][27][28][29][30][31] , and Sn 500 clusters, and Sn nanosolids deposited on Si 3 N 4 substrate as well [64]. Calculations [100] show that the T m transition for Sn 6-13 happens at Sn 7 .…”
Section: Bols Formulationsupporting
confidence: 77%
“…Numerical optimizations suggest that Ga þ 13 and Ga þ 17 clusters melt at 1,400 and 650 K [98] and Sn n (n = 6, 7, 10 and 13) clusters melt at 1,300, 2,100, 2,000, and 1,900 K, respectively [100]. For a Sn 10 cluster, the structural transition happens at 500 and 1,500 K and the structural transition of a Sn 20 Calculations [99] suggested that the IV-A elements, C n , Si n , Ge n , and Sn n (n * 13) clusters melt at temperatures higher than their T m (?). The measured T m for Bi particles of 7 nm in radius was similar, being up to 50 K above the value predicted by the homogeneous melting model [103].…”
Section: Observationsmentioning
confidence: 98%
See 1 more Smart Citation
“…An MD calculation suggested that a 115 K overheating occurs to Pb(111) films confined in an Al(111) matrix [262]. The T m suppression for a free surface is attributed to the reduced degree of confinement, and hence the increased entropy of the molecules at the surface compared with atoms in the bulk, whereas the T m elevation or depression of the embedded nanosolids depends on the coherency between the nanosolids and the embedding matrix [263,264].…”
Section: Outstanding Modelsmentioning
confidence: 99%
“…However, for the embedded NPs the melting point is not only related to NPs' size, structure and shape; but also affected by the embedding matrix. For some matrices, melting of the embedded NPs occurs in lower temperature than its bulk state, while it is possible for the same NPs to have superheating above the melting point in some other matrices [31][32][33][34][35]. Qi et al [36] have developed a new model to accounting for the size and shape dependent superheating of nanoparticles embedded in a matrix where the particle shape is considered by introducing a shape factor.…”
Section: Structural Characterizationmentioning
confidence: 99%